ANALISIS EFEKTIVITAS KINERJA KEUANGAN LEMBAGA NIRLABA STUDI KASUS PADA LEMBAGA BANTUAN HUKUM BANDA ACEH 2020-2021 - Desy Puspita (Jurnal Manajemen, Ekonomi, Keuangan dan Akuntansi, 2023)
This study aims to determine the effective analysis of the financial performance of non-profit institutions for case studies at legal aid institutions in Banda Aceh. The data collection technique is using secondary data, namely documentation. The data analysis technique in this study uses the working capital ratio, current ratio, and Boppo ratio. . The results of the study show that the highest working capital ratio is in 2020, namely 522.95% in the inefficient category and the lowest is in 2021, which is 8.01% and is categorized as very efficient. The Current Ratio in 2020 was 522.95 very effective and in 2021 it was 5.229 ineffective. The highest Boppo was in 2020, namely 118.85%, which was in the very effective category, and the lowest was in 2021, which was 63.28%, which was categorized as less effective.